A comparison of wildlife value orientations and attitudes toward timber rattlesnakes (Crotalus horridus). Issue 1 (2nd January 2020) - Keener-Eck, Lindsay S.; Morzillo, Anita T.; Christoffel, Rebecca A.
ABSTRACT: Human-wildlife interactions can be explained using a cognitive hierarchy model, in which wildlife value orientations (WVO) form the basis for human beliefs, attitudes, and behaviors related to wildlife and wildlife management. In this article, we used data from a mail survey to test the fit of an established WVO framework to a venomous snake species. Study participants were divided into four WVO types (Distanced, Mutualists, Pluralists, Traditionalists). Results indicated that WVO types varied by sex and certain lifestyle factors. Attitudes toward timber rattlesnakes also varied by WVO type. Pluralists exhibited the most favorable attitudes while Traditionalists exhibited the most adverse attitudes toward timber rattlesnakes. Potential for Conflict Index (PCI2 ) analysis revealed variation among members of each WVO type in support for timber rattlesnake management strategies. This segmentation method can help wildlife managers and researchers better understand the diversity of human characteristics related to conservation and management of wildlife species.